Mental Imagery: Competitive Anxiety Control in Karate Kumite Athlete - Herdiansyah Herdiansyah; Tatang Muhtar; Muhammad Nur Alif (STKIP Muhammadiyah Kuningan, 2022)
This study aimed to test the effect of mental imagery training on the competitive anxiety of karate Kumite athletes. One of the benefits of mental imagery is that it can improve the athlete's ability to control psychological symptoms such as anxiety. So that athletes can show their best performance during the game. This research used quantitative methods with an experimental approach, the pretest-posttest control and an experimental group design. The population used West Java regional karate athletes, totalling 42 athletes. Using purposive sampling techniques, the samples consisted of 15 Bandung Karate Club Kumite athletes and 15 Kei Shin Kan Kumite athletes. Data were obtained using The Hogg Eco-Anxiety Scale. Based on the results of the data analysis obtained, the average experimental pretest of 25.20 and posttest of 20.00 showed a decrease in the anxiety of Kumite athletes after being given imagery training. In addition, the N-Gain scores in both groups show decreased pressure in Kumite athletes. However, the N-Gain score in the experimental group was lower than the control group (-23.60 < 3.56), and in the t-test on the N-Gain value, the score obtained the Sig. Value (2-tailed) was 0.005 < α = 0.05. So it can be concluded that imagery training affects the competitive anxiety of Kumite athletes, and there are significant differences in effectiveness in applying imagery training with conventional exercises